Analisis untuk mengenalpasti risiko kejadian lubang benam menggunakan sistem maklumat geografi - Mohd. Saat, Sa'adiah (2006)
This study integrates Geophysical Method, Geographical Positioning System (GPS) and Geographical Information System (GIS) for analysis of sinkhole risk in residential area. The sinkhole phenomena in residential area are related to geological factor, environment and local activities. Analysis of topographical surface is represented visually using GIS data layers. The Geophysical survey (i.e. Resistivity survey using ABEM SAS 4000) was carried out to determine the subsurface structure of the study area. After Resistivity survey, precise locations of sinkhole were determined using GPS Topcon HiPER. All relevant data were converted to GIS (*.shp) format in the same projection system namely RSO (Rectified Skew Orthomorphic), and integrated into a GIS database. Spatial analysis for sinkhole phenomena was developed via GIS applications using ArcGIS components (i.e. ArcMap and ArcObjects), Mapinfo Professional and Microsoft Visual Basic 6.0. The main outcome of the research is a system for analysis for sinkhole risk in residential area via GIS technique.